Organizational Citizenship Behavior (OCB) sebagai Pemediasi pada Pengaruh Kompetensi dan Modal Psikologi (Psychological Capital) terhadap Kinerja - Puja Sulistyawan (Jurnal Ilmiah Aset, 2017)
This research test to influence the competence and psychological capital of performance with OCB mediation by officers of the BPS the Central Java Province.Hypothesis testing of this research use result of multiple linear regression analysis.The research is done by BPS Kendal Regency, Demak Regency, Semarang Regency and Salatiga City. From the beginning, Sample is used in this research 124 officers, but the questionnaire can be analyzed is turned 114. Base on the result of hypothesis test can be concluded. The first, positively influential competence and significance of Organizational Citizenship Behavior (OCB).The second, Psychological Capital influence by positive way and significance of Organizational Citizenship Behavior (OCB). The third, the performance is not influenced by significant competence. The fourth, the performance is influenced by positive way and significance of Psychological Capital. And the last, Organizational Citizenship Behavior (OCB influence to positive way and significance of performance. In this mediation, the result is OCB variable mediate perfectly (full mediated) the influence competence to performance, but the influence of variable capital psychology on performance in another side more effective directly is not through the OCB.